2021
DOI: 10.1108/ijbm-05-2021-0200
|View full text |Cite
|
Sign up to set email alerts
|

Households' intentions under financial vulnerability conditions: is it likely for the COVID-19 pandemic to leave a permanent scar?

Abstract: PurposeThe authors draw on psychological reactance theory, collective mental programming, psychological profiles and financial vulnerability experiences to assess the possibility that the pandemic may induce transformative changes in households' behavioral intentions related to financial decisions after the pandemic is over.Design/methodology/approachUsing a unique survey data drawn from four different countries located in North America, Europe, Africa and Latin America, the authors show that the stressful con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…Clark et al (2021) found that approximately 20% of respondents were financially fragile and had difficulty raising mid-sized emergency funds during the pandemic. Alhenawi and Yazdanparast (2022) asserted that the pandemic left a permanent scar on households, and made them more prone to defensive financial decisions. Based on these discussions, we developed the first hypothesis of the study.…”
Section: Economic Impact Of Covid-19mentioning
confidence: 99%
“…Clark et al (2021) found that approximately 20% of respondents were financially fragile and had difficulty raising mid-sized emergency funds during the pandemic. Alhenawi and Yazdanparast (2022) asserted that the pandemic left a permanent scar on households, and made them more prone to defensive financial decisions. Based on these discussions, we developed the first hypothesis of the study.…”
Section: Economic Impact Of Covid-19mentioning
confidence: 99%
“…As such, researchers have called for the examination of household responses across different economies to explore potential differences between developed and emerging economies (Liu et al, 2020 ). Moreover, extant research has merely examined consumption patterns during the pandemic with little attention to the post‐pandemic changes in consumer behavior (see Alhenawi & Yazdanparast, 2021 for an exception). Furthermore, many studies have largely focused on purchase‐related decisions and ignored other decisions related to interpersonal relationships, individuals' emotional well‐being, and financial situation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Literature suggests that households would heighten their precautionary saving motives and then increase their savings in response to economic recessions and hazardous events because of the aggravation of uncertainties about the future and the worsening of the macroeconomy (e.g., Skidmore, 2001 ; Mody et al, 2012 ; Lydon and McIndoe-Calder, 2021 ; Zhang et al, 2022 ). In addition, from a psychological/behavioral perspective, Alhenawi and Yazdanparast (2021) and Yazdanparast and Alhenawi (2022) find that the COVID-19 pandemic is associated with households’ increases in fears and uncertainties. As COVID-19 vaccination may mitigate households’ uncertainties and boost the macroeconomy, we conjecture that COVID-19 vaccination leads to significant decreases in precautionary saving motives and consequently, in households’ bank savings.…”
Section: Introductionmentioning
confidence: 99%